Hubungan antara Minat Siswa terhadap Kegiatan Pramuka dengan Partisipasinya Mengikuti Kegiatan Pramuka di SMPN 12 Padang - Rezkita Fajriani; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by low of participation student in follow pramuka activity in SMPN 12 Padang. This is caused because the less of interest student about pramuka activty in SMPN 12 Padang, purpose of research the are: (1) to describe of interest student about pramuka activity, (2) to describe of participation studend in followed pramuka activity, (3) to describe of corelation between interest student about pramuka activity with participation student followed pramuka activity in SMPN 12 Padang. This type the research of corelation set of quantitative. Population are 45 student. The research sampel is 75 % of population that are 34 student, the used tekhnik is stratified random sampling. The tekhnik of gathering data in quesioner. Tekhnik analysis data use persentase and product moment. The results showed that: (1) interest student of activty paramuka in SMPN 12 Padang is less categorized, (2) participation student in followed avtivity pramuka is less categorized. (3) be found of signifikan corelation between interest student about pramuka activity with participation student followed pramuka activity in SMPN 12 Padang.Keywords: Interest, Pramuka Activity, Participation